Adulteration of hypoglycemic products: the silent threat - Raniah I. Alnaser; Fawaz A. Alassaf; Mohammed N. Abed (Romanian Journal of Medical Practice, 2023)
Background. The growing tendency toward the adulteration of hypoglycemic products in the market to increase the seller’s profits, the increased promotions of such products by unscrupulous promoters, and the higher rate of consumption by diabetic patients in the community all of these represent an alarm for serious health problems that could be fatal and have a potential threat to public health when using them. Aim. This review aims to attract the attention of the researchers to the hazardous clinical outcomes of adulterated hypoglycemic products and encourage them to do further studies analyzing the compositions of the available hypoglycemic products. Results. Based on the obtained data from the latest studies, the available hypoglycemic products have undeclared and banned anti-diabetic agents that lead to serious side effects. Conclusion. The popularity and abundance of adulterated hypoglycemic products in the market that are claimed to be effective for type 2 diabetes mellitus (Ty2DM) are hazardous to public health and have significant clinical outcomes due to their undeclared anti-diabetic agents which could be lethal to diabetic patients.